A Relationship Between Visual Complexity and Aesthetic Appraisal of Car Front Images: An Eye-Tracker Study. (August 2015) - Chassy, Philippe; Lindell, Trym A. E.; Jones, Jessica A.; Paramei, Galina V.
Image aesthetic pleasure (AP) is conjectured to be related to image visual complexity (VC). The aim of the present study was to investigate whether (a) two image attributes, AP and VC, are reflected in eye-movement parameters; and (b) subjective measures of AP and VC are related. Participants ( N = 26) explored car front images ( M = 50) while their eye movements were recorded. Following image exposure (10 seconds), its VC and AP were rated. Fixation count was found to positively correlate with the subjective VC and its objective proxy, JPEG compression size, suggesting that this eye-movement parameter can be considered an objective behavioral measure of VC. AP, in comparison, positively correlated with average dwelling time. Subjective measures of AP and VC were related too, following an inverted U-shape function best-fit by a quadratic equation. In addition, AP was found to be modulated by car prestige. Our findings reveal a close relationship between subjective and objective measures of complexity and aesthetic appraisal, which is interpreted within a prototype-based theory framework.